The Effects of Language Experience and Speech Context on the Phonetic Accommodation of English-accented Spanish Voicing. (March 2017) - Llanos, Fernando; Francis, Alexander L
Native speakers of Spanish with different amounts of experience with English classified stop-consonant voicing (/b/ versus /p/) across different speech accents: English-accented Spanish, native Spanish, and native English. While listeners with little experience with English classified target voicing with an English- or Spanish-like voice onset time (VOT) boundary, predicted by contextual VOT, listeners familiar with English relied on an English-like VOT boundary in an English-accented Spanish context even in the absence of clear contextual cues to English VOT. This indicates that Spanish listeners accommodated English-accented Spanish voicing differently depending on their degree of familiarization with the English norm.